2005
DOI: 10.1136/ard.2004.033399
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic and metabolite measurements are associated with clinical status in patients with rheumatoid arthritis treated with methotrexate: results of a multicentred cross sectional observational study

Abstract: Objective: To investigate the contribution of red blood cell (RBC) methotrexate polyglutamates (MTX PGs), RBC folate polyglutamates (folate PGs), and a pharmacogenetic index to the clinical status of patients with rheumatoid arthritis treated with MTX. Methods: 226 adult patients treated with weekly MTX for more than 3 months were enrolled at three sites in a multicentred cross sectional observational study. Clinical status was assessed by the number of joint counts, physician's global assessment of disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
112
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 30 publications
11
112
1
3
Order By: Relevance
“…There are certainly other mechanisms yet to be discovered that may be contributing to this phenomenon. If higher concentrations of long-chain MTXGlu [3][4][5] are truly associated with improvement in disease, as some authors have suggested (16)(17)(18), these findings would support the use of subcutaneous dosing for more patients. However, prospective studies evaluating the effect of route of MTX administration on cellular folate status will be necessary to confirm this notion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are certainly other mechanisms yet to be discovered that may be contributing to this phenomenon. If higher concentrations of long-chain MTXGlu [3][4][5] are truly associated with improvement in disease, as some authors have suggested (16)(17)(18), these findings would support the use of subcutaneous dosing for more patients. However, prospective studies evaluating the effect of route of MTX administration on cellular folate status will be necessary to confirm this notion.…”
Section: Discussionmentioning
confidence: 98%
“…Recent literature suggests that intracellular MTX polyglutamation may be correlated with the efficacy of MTX in adult patients with rheumatoid arthritis (RA) (16)(17)(18). One may also speculate that increased intracellular concentrations of MTX contribute to the risk of toxicity, but this has not been rigorously evaluated to date.…”
mentioning
confidence: 99%
“…[6][7][8] In the present study, we examined the association between RFC-1 G80A polymorphism and treatment outcome in patients with RA administered MTX.…”
Section: Introductionmentioning
confidence: 99%
“…Serum MTX concentrations have been shown to have no correlation with disease activity (19). However, recent studies suggest a correlation between RBC MTXGlu n concentrations and disease activity (18,20,21). The first of these studies in 65 patients with RA showed that RBC MTXGlu 1-5 concentrations were significantly higher in responders (mean Ϯ SD 60.7 Ϯ 18.9 nmoles/liter) and partial responders (50.8 Ϯ 23.3 nmoles/liter) to treatment than in nonresponders (21.5 Ϯ 10.5 nmoles/liter) (20).…”
mentioning
confidence: 99%
“…The first of these studies in 65 patients with RA showed that RBC MTXGlu 1-5 concentrations were significantly higher in responders (mean Ϯ SD 60.7 Ϯ 18.9 nmoles/liter) and partial responders (50.8 Ϯ 23.3 nmoles/liter) to treatment than in nonresponders (21.5 Ϯ 10.5 nmoles/liter) (20). The initial study by Dervieux and colleagues (18) of 108 patients was then extended to 226 patients (21), and patients with RBC MTXGlu 3 levels Ͻ60 nmoles/liter were more likely to have a poor clinical response. In addition, in a small group of 23 patients commencing MTX treatment, a higher RBC MTXGlu 3 concentration at 3 months was associated with a greater chance of better disease control at 6 months (22).…”
mentioning
confidence: 99%